2019
DOI: 10.1097/meg.0000000000001458
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic radiation forced impulse-based splenic prediction model using data mining for the noninvasive prediction of esophageal varices in hepatitis C virus advanced fibrosis

Abstract: Background Esophageal varices (EV) are serious complications of hepatitis C virus (HCV) cirrhosis. Endoscopic screening is expensive, invasive, and uncomfortable. Accordingly, noninvasive methods are mandatory to avoid unnecessary endoscopy. Acoustic radiation forced impulse (ARFI) imaging using point shear wave elastography as demonstrated with virtual touch quantification is a possible noninvasive EV predictor. We aimed to validate the reliability of liver stiffness (LS) and spleen stiffness (SS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…A number of studies have investigated spleen stiffness as a non‐invasive parameter for portal hypertension 24–26 . In a recent trial, elevated spleen stiffness measured by ARFI (S‐ARFI) represented a reliable non‐invasive tool for the prediction of oesophageal varices in HCV‐infected patients 27 …”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have investigated spleen stiffness as a non‐invasive parameter for portal hypertension 24–26 . In a recent trial, elevated spleen stiffness measured by ARFI (S‐ARFI) represented a reliable non‐invasive tool for the prediction of oesophageal varices in HCV‐infected patients 27 …”
Section: Introductionmentioning
confidence: 99%
“…Fierbinteanu- Braticevici C et al showed the AUROC for the detection of EVs using SS was 0.776 [53]. SS is suggested to be superior to LS in detecting EVs [54,55,56 ▪ ]. However, in studies of Munoz-Codoceo C and others, LS and SS are suboptimal or only have modest accuracy for detecting varices [57 ▪ ,58,59].…”
Section: The Diagnosis Of Small Varicesmentioning
confidence: 98%
“…Therefore, exploring the best frequency of breast elastic ultrasound is highly important for improving its diagnostic value. Previous research results showed that objective and quantitative imaging indexes could effectively reflect the prognosis or prediction of the disease [6][7][8]. Moreover, the diagnosis based on a combination of multiple indexes is more promising than the diagnosis based on a single index, and it is good enough to affect clinical decisions.…”
Section: Introductionmentioning
confidence: 99%